Epidural Anesthesia for Cesarean Section in a Pregnant Woman with Marfan Syndrome and Dural Ectasia - Franco Pepe; Mariagrazia Stracquadanio; Francesco De Luca; Agata Privitera; Elisabetta Sanalitro; Puccio Scarpinati (Hindawi Limited, 2017)
Marfan syndrome (MFS) is a genetic disorder of connective tissue, characterized by variable clinical features and multisystem complications. The anesthetic management during delivery is debated. Regional anesthesia has been used with success during cesarean delivery, but in some MFS patients there is a probability of erratic and inadequate spread of intrathecal local anesthetics as a result of dural ectasia. In these cases, epidural anesthesia may be a particularly useful technique during cesarean delivery because it allows an adequate spread and action of local anesthetic with a controlled onset of anesthesia, analgesia, and sympathetic block and a low risk of perioperative complications. We report the perioperative management of a patient with MFS and dural ectasia who successfully underwent cesarean section using epidural technique anesthesia. The previous pregnancy of this woman ended with cesarean section with a failed spinal anesthesia that was converted to general anesthesia due to unknown dural ectasia at that time.